Chiral resolution and enantioselectivity of synthetic cathinones: A brief review - Silva B. (2018)
Chiral discrimination has become one of the most important fields in analytical and medicinal chemistry, and forensic toxicology. The enantiomers may have different binding to proteins that may lead to many pharmacological and toxicological differences between them, including kinetic (at the absorption, distribution, metabolism and excretion level) or dynamic (level of potency and efficacy or even differences in mechanism of action) variations. Cathinone derivatives are chiral compounds, sold via the internet for recreational use, and little is known about their enantiomeric selectivity. Consequently, it is of crucial importance for the development of resolution methods to obtain pure enantiomers to study their biological effects. In the last few years, techniques for chiral drug analysis, as chromatography, have been developed and some works related to the analytical enantiomeric resolution of synthetic cathinones were described. However, information about synthetic cathinones in the literature is scarce specially concerning single enantiomers. In this mini-review, analytical chiral resolution and biological differences between enantiomers of cathinone derivatives will be addressed. © The Author 2017. Published by Oxford University Press. All rights reserved.